PEP-1-FK506BP12 inhibits matrix metalloproteinase expression in human articular chondrocytes and in a mouse carrageenan-induced arthritis model - Hwang, Hyun Sook (BMB Rep, 2015)
The 12 kDa FK506-binding protein (FK506BP12), an immunosuppressor, modulates T cell activation via calcineurin inhibition. In this study, we investigated the ability of PEP-1-FK506BP12, consisting of FK506BP12 fused to the protein transduction domain PEP-1 peptide, to suppress catabolic responses in primary human chondrocytes and in a mouse carrageenan-induced paw arthritis model. Western blotting and immunofluorescence analysis showed that PEP-1-FK506BP12 efficiently penetrated chondrocytes and cartilage explants. In interleukin-1β (IL-1β)-treated chondrocytes, PEP-1-FK506BP12 significantly suppressed the expression of catabolic enzymes, including matrix metalloproteinases (MMPs)-1, -3, and -13 in addition to cyclooxygenase-2, at both the mRNA and protein levels, whereas FK506BP12 alone did not. In addition, PEP-1-FK506BP12 decreased IL-1β-induced phosphorylation of the mitogen-activated protein kinase (MAPK) complex (p38, JNK, and ERK) and the inhibitor kappa B alpha. In the mouse model of carrageenan-induced paw arthritis, PEP-1-FK506BP12 suppressed both carrageenan-induced MMP-13 production and paw inflammation. PEP-1-FK506BP12 may have therapeutic potential in the alleviation of OA progression. [BMB Reports 2015; 48(7): 407-412]